PERSEPSI SISWA TERHADAP PEMBELAJARAN DARING MATA PELAJARAN EKONOMI PADA MASA PANDEMI COVID-19 KELAS XI SMA NEGERI 1 BONTANG - Muhammad Fauzan Rachman; Sudarman Sudarman; Noor Ellyawati; Ratna Fitri Astuti (PROMOSI (Jurnal Pendidikan Ekonomi), 2022)
The purpose of this research is to determine the implementation of online learning on economicslearning during the Covid-19 pandemic by the eleventh grader of social studies major at SMA Negeri 1 Bontang. This research is also to find out students' perceptions of applications, tools, and networks used in online learning. This is a case study researchby using qualitative approach. The data sources in this study were eight students from class XI IPS and oneeconomics teacher. This research used purposive sampling technique. Meanwhile, the data collection techniqueused interview, questionnaires and documentation techniques.The research’s finding showed promising result in terms of availability of tools. Cellphone and laptop are the tools used in online learning. The students also showed the capability to use online learning application such as Whatsapp and Google Classroom. The research also showed that students tend to be more interested in using Google Classroom.  Learning process indicators demonstrated the range of student preferences for online learning concepts. There are two dominant concepts. The first is lectures, in which students gain a better understanding of the topic through the teacher's explanation. The second is online learning in the form of videos. The content in the form of a video is more entertaining than reading content.The fulfillment of online learning resources for all students, particularly mobile devices, demonstrates extremely high outcomes in the support indication. Support from schools is also provided, such as internet bundles, textbooks, and instruction on how to utilize online learning media apps. Students are also feeling the support of their parents. The establishment of a parent Whatsapp group by the homeroom teacher is as a school partner in overseeing the student learning process. Keywords: Perception, Online Learning, Covid-19 Pandemic